Vegetation type and demography of low density willow ptarmigan populations. Issue 1 (5th October 2016) - Kvasnes, Mikkel Andreas Jørnsøn; Pedersen, Hans Christian; Storaas, Torstein; Nilsen, Erlend Birkeland
ABSTRACT: The willow ptarmigan ( Lagopus lagopus ) is an economically important and desired game species in Scandinavia. Its abundance varies considerably in time and space, but there has been a long‐term population decline over recent decades. Earlier studies demonstrated willow ptarmigan select certain habitat features. We investigated the relationship between area‐specific conditions (habitat and ownership status) and 2 variables describing willow ptarmigan demography (adult density and reproductive success). We found no connection between adult density and cover of 6 vegetation types. However, willow ptarmigan had lower reproductive success in survey areas dominated by mountain birch ( Betula pubescens czerepanovii ) forest. The lack of any clear association between willow ptarmigan density and vegetation types could be explained by relatively low population densities in our study areas. Thus, relative to years with higher population levels, resources (e.g., food and shelter) were plentiful and competition was low. We found strong indications in areas of similar vegetation composition that adult density was higher in areas managed by private landowners than on state‐owned land. The difference in density was 2.56 birds/km 2, equivalent to a 46% increase compared to adult density on state‐owned land. This difference in density may be due to a difference in hunting pressure. We conclude that management actions to improve habitat will have little effect on willow ptarmigan populations during periods of relatively low densities. © 2016 The Wildlife Society. Abstract : We found no clear connection between density of adult willow ptarmigan and vegetation types, but density was higher on private land than on state‐owned land and willow ptarmigan had lower reproductive success in areas dominated by mountain birch. Our study suggests that habitat was not limiting in our study areas and that management actions aiming to improve habitat will have little effect on willow ptarmigan populations during periods of relatively low densities.